Blended Learning in ELT Focused on the Development of Speaking Skills - Kozderová, Nikola (Univerzita Pardubice, 2022)
Living in the 21st century, nobody can deny the importance of information and communication technology in almost all aspects of daily life including the way we work, shop, communicate and even educate ourselves as well as the younger generations. This bachelor thesis deals with the opportunities for the development of speaking skills in English language teaching for secondary school students in the concept of blended learning. In the theoretical part, the key terms blended learning, communicative competence, speaking, and ICT are defined. The use of ICT in education is then put into the context of the Strategy for the Education Policy of The Czech Republic up to 2030+. In the practical part of the thesis, the process of planning an English lesson is described. The lesson plans including speaking activities during which ICT is used can be found in the appendices.
Blended learning ve výuce anglického jazyka: zaměřeno na rozvoj řečových dovedností
Keywords: kombinovaná výuka; komunikativní kompetence; řečová dovednost mluvení; informační a komunikační technologie; blended learning; communicative competence; speaking; ICT